Global-optimized energy storage performance in multilayer ferroelectric ceramic capacitors - Da Li; Zhaobo Liu; Weichen Zhao; Yan Guo; Zhentao Wang; Diming Xu; Houbing Huang; Li-Xia Pang; Tao Zhou; Wen-Feng Liu; Di Zhou (Nature Communications)
Abstract Multilayer ceramic capacitor as a vital core-component for various applications is always in the spotlight. Next-generation electrical and electronic systems elaborate further requirements of multilayer ceramic capacitors in terms of higher energy storage capabilities, better stabilities, environmental-friendly lead-free, etc., where these major obstacles may restrict each other. An effective strategy for energy storage performance global optimization is put up here by constructing local polymorphic polarization configuration integrated with prototype device manufacturing. A large energy density of 20.0 J·cm−3 along with a high efficiency of 86.5%, and remarkable high-temperature stability, are achieved in lead-free multilayer ceramic capacitors. The strategy provides a feasible routine from nano, micro to macro regions in manipulating local polarizations, domain-switching barriers and breakdown strength, illustrating its great potential to be generally applicable in the design of high-performance energy storage multilayer ceramic capacitors.